Three-band perfect absorber with high refractive index sensing based on an active tunable Dirac semimetal. Issue 32 (5th August 2021) - Li, Zhiyou; Yi, Zao; Liu, Tinting; Liu, Li; Chen, Xifang; Zheng, Fusheng; Zhang, Jianguo; Li, Hailiang; Wu, Pinghui; Yan, Peiguang
Abstract : We designed a perfect absorber based on bulk Dirac semi-metallic. The minimum bandwidth is 0.02 THz, the maximum quality factor is 106, and the maximum refractive index sensitivity is 0.1525 THz RIU −1 . The device can be tuned by Fermi level. Abstract : In this paper, we designed a three-band narrowband perfect absorber based on bulk Dirac semi-metallic (BDS) metamaterials. The absorber consists of a hollow Dirac semi-metallic layer above, a gold layer below and a photonic crystal slab (PCS) in the middle. The study found that the terahertz wave absorber achieved three perfect absorption rates of more than 95% in the range of 1 to 2.4 THz. The minimum bandwidth (FWHM) is 0.02 THz, and the maximum quality factor ( Q ) is 106. A reasonable explanation of high absorption can be obtained by impedance matching, electric dipole and other principles. The absorption spectra of the two polarizations show different responses at different incident angles. In addition, we also obtained the influence of the structural parameters of the upper layer of the metamaterial on the absorption performance. We defined the refractive index sensitivity ( S ) with a maximum sensitivity of 0.1525 THz RIU −1 and a highest quality factor (FOM) of 4.26 in the refractive index range of 1 to 1.8. The maximum adjustable range is 0.06 THz in the Fermi energy range of 60 to 140 meV. Because of its excellent characteristics, our absorber will have good development prospects in the fields of optical switching, biochemical imaging, and space detection.